2020
DOI: 10.3390/molecules25225266
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Low Molecular Weight Compounds, Iron and Copper of Wine Spirit Aged with Chestnut Staves under Different Levels of Micro-Oxygenation

Abstract: Alternative technologies for a more sustainable wine spirits’ ageing have been studied but a lack of knowledge on the effect of oxygenation level remains. This work examined the behaviour of low molecular weight compounds, iron and copper of a wine spirit aged in 50 L demijohns with chestnut wood staves combined with three levels of micro-oxygenation or nitrogen. Compounds and mineral elements were quantified by HPLC and FAAS, respectively, in samples collected at 8, 21, 60, 180, 270 and 365 days of ageing. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 58 publications
7
27
0
Order By: Relevance
“…In the first ANOVA performed (Table 1), the toasting level also had a significant effect on the physicochemical characteristics and on some volatile compounds. This effect was already noticed for wine spirit aged at an industrial scale by other authors [54,55]. They reported an increasing trend of some volatile and low molecular weight compounds over the ageing time.…”
Section: Ftir-atr Analysissupporting
confidence: 71%
“…In the first ANOVA performed (Table 1), the toasting level also had a significant effect on the physicochemical characteristics and on some volatile compounds. This effect was already noticed for wine spirit aged at an industrial scale by other authors [54,55]. They reported an increasing trend of some volatile and low molecular weight compounds over the ageing time.…”
Section: Ftir-atr Analysissupporting
confidence: 71%
“…More recently, the combination of wood fragments with micro-oxygenation (MOX), in an attempt to simulate what is happening in a wooden barrel, has shown that it is possible to accelerate the ageing process in comparison with the conventional process, enabling to obtain higher quality spirits [24,25]. These studies confirmed the importance of oxygen in the ageing process.…”
Section: Of 15mentioning
confidence: 93%
“…The dissolved oxygen content in each modality was controlled over the time, as described previously [24] and the values are shown in Figure 1.…”
Section: Wine Spirit Samples and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations